Synthesis parameters and transfer techniques of mono-few layer graphene for transparent conductive electrode - Kang, C.H. (Institute of Electrical and Electronics Engineers Inc., 2017)
Properties of high quality graphene synthesized using chemical vapor deposition (CVD) are reported. Parameters such as the rate and time of gas flow are varied during synthesis. The as-grown graphene is then transferred onto oxidized silicon substrate by employing single and double layer polymer-based techniques. Next, surface morphology, electrical and optical properties of the synthesized mono-few layer graphene are characterized using optical microscope, Raman spectroscopy, UV-VIS spectroscopy, and four-point probe measurement. Results show that by using the appropriate combination of synthesis parameters and transfer technique, high quality graphene with electrical sheet resistance as low as 900 Ω/sq and optical transparencies as high as 94 can be obtained. Such quality graphene is highly desirable as transparent conductive electrodes in applications like light emitting diodes, solar cells and optical sensors. © 2016 IEEE.